Geografia do crime : homicídios e aspectos demográficos no Brasil e estado do Espírito Santo - Lira, Pablo Silva (2019)
The gradual increase in homicides observed since the mid-1980s in Brazil, and the current rates identified, make it undeniable the need to develop studies and research that provide a better understanding of the phenomenon of lethal violent crime. Researchers in the field of public security, such as Waiselfisz (2014) and Cerqueira (2014), point out that the main victims and perpetrators of homicides are mostly young men, aged 15-29 years, afro-descendants and residents of spaces considered underprivileged from a social, economic and infrastructural prism. These characteristics reveal a demographic pattern of violent crime, here represented by homicides. The purpose of this research is to deepen the analysis and etiology of homicides from a demographic perspective. By taking space as a central category, geography reveals a vast theoretical field and a set of spatial analysis tools that favor the foundation of theses on lethal violent crime. In addition, demography tends to contribute to the investigation of population characteristics that explain the social matrix that gives rise to the violence translated by homicides. The hypothesis admitted in this study is that the variation of homicides is explained by demographic aspects. Based on this premise, the following questions are presented: Do demographic aspects contribute to explain the spatial and temporal variation of homicides? If the answer to this guiding question is positive, which demographic factor has the greatest explanatory potential? And to what extent does this aspect influence homicide? The bibliographic discussion presented here is based on the research on crime, which highlights the geography of crime and demographic studies. The econometric methods employed by Mello and Schneider (2007) and Cerqueira and Moura (2014) are used as initial theoretical-methodological references to develop and operationalize analyzes of homicides and demographic aspects in our empirical model within the Federal Units (UFs) and of the municipalities of the state of Espírito Santo, through the databases of the Mortality Information System (SIM/DATASUS), Brazilian Institute of Geography and Statistics (IBGE), among others. The results of such an empirical model are taken as a starting point for the development of geographic-statistical analyzes. Among the main results obtained, we corroborate that certain demographic aspects, such as demographic density, the proportion of suitable households, the proportion of immigrants, the proportion of young men and the educational conditions of the population, explain, in part, the variation of homicides.